MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMA PADA MATERI MITIGASI BENCANA ALAM - Lukman, Syahril; Muhammad, Hujairah Hi (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
This research was conducted against the background of the low learning outcomes of class XI IPS students at SMA Negeri 6 Ternate City on natural disaster mitigation material, therefore student learning outcomes need to be improved. One way to improve student learning outcomes is through implementing the role playing learning model so that students can participate actively in the learning process by acting out a role in accordance with the natural disaster mitigation scenario for Gamalama volcano that has been prepared, so that student learning outcomes increase. This research is Classroom Action Research (PTK) with a cycle model that is carried out repeatedly and continuously consisting of planning, implementation, observation and reflection. The subjects of this research were 21 students in class XI IPS. Data collection was carried out by observation and tests. Based on the research results, it is known that student learning outcomes have increased after implementing the role playing learning model. This can be seen from the increase in students' classical learning completeness in cycle I by 71.43% and cycle II by 90.48%. Experienced an increase from cycle I to cycle II of 19.05%. Thus it can be concluded that the role playing learning model can improve student learning outcomes.